Defining digital literacy development: An examination of pre-service teachers’ beliefs - List, Alexandra (Computers and education, 2019)
We identify three conceptions of digital literacy development populating the literature: digital natives, skill-based, and sociocultural perspectives. We adopt a qualitative approach to examine pre-service teachers' beliefs about digital literacy development as aligned with each of these three perspectives. While pre-service teachers were most commonly found to hold skill-based perspectives on digital literacy development, digital natives aligned and sociocultural perspectives were also well-represented. We further identify perspectives on digital literacy development uniquely appearing in students' responses. These include pre-service teachers’ conception of digital literacy development as autonomously developed, technology driven, or project based. We further examine the contexts within which pre-service teachers situate digital literacy as emerging; these include both formal and informal settings. The article concludes with a discussion of implications for instruction. •Pre-service teachers' beliefs about digital literacy development are investigated in reference to the extant literature.•Pre-service teachers' beliefs reflected digital natives, skill-based, and sociocultural perspectives.•Additional conceptions of digital literacy development were identified (e.g., technology driven).•The contexts within pre-service teachers situate their digital literacy development were further examined.